2020
DOI: 10.1109/access.2020.2982224
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-the-Art Review on Image Synthesis With Generative Adversarial Networks

Abstract: Generative Adversarial Networks (GANs) have achieved impressive results in various image synthesis tasks, and are becoming a hot topic in computer vision research because of the impressive performance they achieved in various applications. In this paper, we introduce the recent research on GANs in the field of image processing, including image synthesis, image generation, image semantic editing, image-to-image translation, image super-resolution, image inpainting, and cartoon generation. We analyze and summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(55 citation statements)
references
References 92 publications
0
55
0
Order By: Relevance
“…Recent approaches [9], [14], [31]- [33] of image-to-image translation use paired input-output examples to learn a mapping function applying a GAN based method. And more recent approaches [6], [8], [15]- [17] use the unpaired setting to learn a parametric translation function that does not need paired data samples.…”
Section: B Image-to-image Translationmentioning
confidence: 99%
“…Recent approaches [9], [14], [31]- [33] of image-to-image translation use paired input-output examples to learn a mapping function applying a GAN based method. And more recent approaches [6], [8], [15]- [17] use the unpaired setting to learn a parametric translation function that does not need paired data samples.…”
Section: B Image-to-image Translationmentioning
confidence: 99%
“…Several articles [21,22,34,[47][48][49] have recently surveyed generative adversarial networks and GAN variants, including image synthesis as an application. Other surveys [50,51] covered image synthesis with GANs and partially discussed image-to-image translation. The effort closest to this survey is that of [50], where authors discussed image synthesis, including few image-to-image translation methods.…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…Other surveys [50,51] covered image synthesis with GANs and partially discussed image-to-image translation. The effort closest to this survey is that of [50], where authors discussed image synthesis, including few image-to-image translation methods.…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…Much research work regarding GANs has been done in designing architectures and training methods which leverage the quality of the generated images, as in StyleGAN2 [6], which uses a special style-based generator to produce high-resolution images. A comprehensive review of state-of-the-art GANs for various image processing tasks can be found in [8].…”
Section: Introductionmentioning
confidence: 99%